Pengembangan Sistem Publikasi Jurnal berbasis Open Journal System Studi Kasus STT Terpadu Nurul Fikri - Nihlah Karimah; Amalia Rahmah (Jurnal Informatika Terpadu, 2020)
The use of information systems properly to support internal activities is one factor for the success and progress of higher education. One of them is the use of information systems to facilitate academicians in documenting scientific articles. STT Terpadu Nurul Fikri already has an e-journal system with an essential role as a storage container for scientific journal collections. One of the applications used to document scientific articles is Open Journal Systems (OJS). However, the information obtained from interviews with e-journal developers and seeing the current condition of e-journals shows that it has not given maximum influence in carrying out its function. The author improves the appearance and content of the content, the e-journal socialization strategy to the internal academic community, and knows the constraints and evaluation methods when migrating to OJS 3. So that, later it is hoped that it will produce an even better e-journal 2.0. In this study, the author has developed and improved the STT-NF e-journal website by going through several stages. Starting from a preliminary study, conducting analysis, making a system display design, implementing, testing with black-box and UAT methods, evaluation and improvement results, to the socialization process of the new e-journal 2.0. Some of the researchers' features to improve and implement were the addition of ISSN number, Current Issue, About the Journal, and Article Template. However, there is one feature that has not been successfully created is the statistics counter feature. Due to this feature using dummy data.